The Drop of Relative Velocity Variation and Coherence Values Prior to Sinabung 2013 Eruptions - Yasa Suparman; Afnimar Afnimar; Devy Kamil Syahbana (Indonesian Journal on Geoscience, 2021)
DOI: 10.17014/ijog.8.1.109-117The cross-correlations of ambient seismic noise at Sinabung Volcano were analyzed from February 2013 to February 2014. Many eruptions occurred during these periods, started on 15 September 2013. Looking at the variations in the coda of the correlations, two types of measurements can be distinguished associated to two types of changes: relative velocity variation and waveform decoherence. The drop of relative velocity variations and waveform decoherence were observed for each station pair of Sinabung one to two months before the first eruption. These changes in accordance to the deformation of the Sinabung edifice were estimated from geodetic measurements, since an analysis of baseline change between GPS stations indicated an inflation of the volcanic edifice prior to September 2013 eruption. The monitoring of relative velocity variations and decoherence provides insights into the ongoing processes in the volcanic edifice to assist in determining the level of volcanic activity.